PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN ASTAGINA RESORT VILLA AND SPA BALI (Studi Pada Astagina Resort Villa And SPA Bali) - Gunawan Wibisono; A.A Ketut Sri Asih; Bagus Ketut Riska Mahawira (Universitas Triatma Mulya, 2020)
This study aims to determine the effect of work discipline and work environment on employee performance of Astagina Resort Villa and Spa Bali. The questionnaire distributed to 80 respondents was all members of the population. This study, using regression analysis techniques by testing hypotheses using T Test and F Test. The results of the T Test show that work discipline has a positive and significant effect on the performance of employees of Astagina Resort Villa and Spa Bali. This is seen from the results of the regression coefficient X1 (b1) thitung = 7.949> t table (0.05: 77) = 1.665 and sig t = 0,000 (p <0.05). Work Environment has a positive and significant effect on employee performance at Astagina Resort Villa and Spa Bali. This is seen from the results of the regression coefficient X2 (b2) t count = 4.624> t table (0.05: 77) = 1.665 and sig t = 0.000 (p <0.05). Work discipline has more dominant influence on employee performance of Astagina Resort Villa and Spa Bali.